ESTIMULAÇÃO PRECOCE DA CRIANÇA E PSICANÁLISE - Santos, Emanuel Dos; Bonamigo, Elenita Costa Beber; Fernandes, Simoni Antunes; Henz, Mariane; Marquesin, Mylena Wichinheski (Salão do Conhecimento, 2017)
Projeto De Extensão Interdisciplinar da Unijuí de Atenção à Saúde da Criança